The Role of Place Names in the Production of Other New Place Names (Name of Kani as an example) - سالار نه‌ریمان ئاغا, شادمان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The paper is a comprehensive attempt to identify the phenomenon of place names in Kurdish language. The research consists of an introduction and two parts with the results that the researcher found and the references list. Introduction: in the introduction, the significance of the research is presented. First part: in this part, the methods of word formation in Kurdish language are clarified with examples. The second part: is the significance and role of basic place names in forming new place names. Then a glossary is organised with 500 compound names with some proven scientific results in the result section. The significance of the study is that it becomes a basis and a source for Kurdish Language for producing more names of this type. Thus, based on that factor, Kurdish language is an agglutinative language. Therefore, the place name (kani) spring, for example, can take a thousand words as determinative for producing more place names and new names. The paper is a comprehensive attempt to identify the phenomenon of place names in Kurdish language. The research consists of an introduction and two parts with the results that the researcher found and the references list. Introduction: in the introduction, the significance of the research is presented. First part: in this part, the methods of word formation in Kurdish language are clarified with examples. The second part: is the significance and role of basic place names in forming new place names. Then a glossary is organised with 500 compound names with some proven scientific results in the result section. The significance of the study is that it becomes a basis and a source for Kurdish Language for producing more names of this type. Thus, based on that factor, Kurdish language is an agglutinative language. Therefore, the place name (kani) spring, for example, can take a thousand words as determinative for producing more place names and new names.